Shaping of porous mullite green bodies by foaming and thermal gelation of bovine serum albumin - Sandoval, María Laura (2015)
The shaping of cellular microstructures of mullite bodies prepared by thermo-gelation of foamed mullite-bovine serum albumin (BSA) suspensions using both a novel forming route and the conventionally reported route were studied. Mullite-BSA and mullite-BSA-methylcellulose (MC) suspensions specific for each route were prepared and then characterized by measuring viscosity. They were subsequently foamed by stirring, and their foaming capacity and foam stability over time were evaluated. Bubble size distributions vs. stand time were obtained by analyzing images captured by confocal laser-scanning microscopy (CLSM). Green bodies were formed by pouring each system into heated molds, by heating and by drying, and were characterized by porosity measurements and microstructural analysis by SEM. The obtained results showed that the use of certain experimental conditions for each route allowed the shaping of homogeneous mullite porous bodies with different microstructural features, namely, ceramic foams with open cells or cellular ceramics with closed cells and thick walls.